Assessment scale of risk for surgical positioning injuries - Camila Mendonça de Moraes Lopes; Vanderlei José Haas; Rosana Aparecida Spadoti Dantas; Cheila Gonçalves de Oliveira; Cristina Maria Galvão
ABSTRACT Objective: to build and validate a scale to assess the risk of surgical positioning injuries in adult patients. Method: methodological research, conducted in two phases: construction and face and content validation of the scale and field research, involving 115 patients. Results: the Risk Assessment Scale for the Development of Injuries due to Surgical Positioning contains seven items, each of which presents five subitems. The scale score ranges between seven and 35 points in which, the higher the score, the higher the patient's risk. The Content Validity Index of the scale corresponded to 0.88. The application of Student's t-test for equality of means revealed the concurrent criterion validity between the scores on the Braden scale and the constructed scale. To assess the predictive criterion validity, the association was tested between the presence of pain deriving from surgical positioning and the development of pressure ulcer, using the score on the Risk Assessment Scale for the Development of Injuries due to Surgical Positioning (p<0.001). The interrater reliability was verified using the intraclass correlation coefficient, equal to 0.99 (p<0.001). Conclusion: the scale is a valid and reliable tool, but further research is needed to assess its use in clinical practice.